Removal of Malachite Green from Aqueous Solution by Activated Carbon Developed from Cocoa (Theobroma Cacao) Shell - A Kinetic and Equilibrium Studies - C. Theivarasu; S. Mylsamy (E-Journal of Chemistry)
The removal of malachite green (MG) by cocoa (Theobroma cacao) shell activated carbon (CSAC) was investigated in present study. Adsorption studies were performed by batch experiments as a function of process parameters such as initial pH, contact time, initial concentration and adsorbent dose. A comparison of kinetic models applied to the adsorption of MG on CSAC was evaluated for the pseudo-first order and pseudo-second order kinetic models. Results showed that the pseudo-second order kinetic model was found to correlate the experimental data well. The experimental equilibrium adsorption data was represented with Langmuir, Freundlich, Tempkin, Dubinin-Radushkevich and Flory-Huggins isotherms. The experimental data obtained in the present study indicated that activated carbon developed from cocoa shell can be attractive options for dye removal from waste water.